20th anniversary of the history of genetic research on cave lions: A short review - Artem Nedoluzhko; Gennady Boeskorov; Alexei Tikhonov; Albert Protopopov (Earth History and Biodiversity)
The Panthera genus originated in Africa and subsequently spread to Eurasia, North America and South America. Species within this genus occupy dominant positions in ecological and food chains, but due to climatic fluctuations, changing ecosystems and various other ecological factors, several Panthera species have become extinct. The cave lion (Panthera spelaea Goldfuss) is one of the iconic species of Pleistocene megafauna, and its genetic research began around twenty years ago. Despite the information available so far, a number of issues regarding taxonomy, microevolutionary processes in populations, and the causes of extinction at the boundary between the Pleistocene and Holocene for this top predator remain unclear. This review aims to systematize the available data on cave lion genetics and develop new directions for studying this animal, as well as considering the genetic prospects for lion survival in the Holocene period.